ANALISIS KECAKAPAN KOMUNIKASI PESERTA DIDIK MELALUI MEDIA KARIKATUR LINGKUNGAN - Sisean Baga; Agung Purwanto; Setia Budi (Universitas Indraprasta PGRI, 2022)
This study aims to determine the students' communication skills through the use of environmental caricature media at one of Junior High School in the city of West Jakarta, Indonesia. The.method used in this study is quasi-experimental, using two groups, pre-test and post-test. The subject in this study was class X.1 dan X.2. The research sample is taken from two classes, which consist of 18 students in each class, through purposive sampling. The t-test analysis shows 0.02 significant value in 0.05 significance level (0.02 < 0.05), so that H0 is rejected. This means there is an effect of using environmental caricature media as a learning resource on students' communication skills. Attractive images in the caricatures can stimulate students to discuss the meaning behind the media with one another. The discussion process that is done in discussing the meaning behind that caricature shows up the student's communication skills with both written or verbal. Students in groups are required to express what they have understood based on the given caricatures. That makes students more familiar in being brave to tell out their opinions with both written or verbal. It can be concluded. that the use of this environmental caricature media influences students' communication skill in both written and oral aspects